EFL Students’ Ability to Identify Singular and Plural Nouns in Paragraph - Nurma Dhona Handayani, Frangky Silitong (Universitas Muhammadiyah Jember, 2017)
This research aims to describe the ability of students to identify singular and plural nouns in the paragraph. The researchers use random sampling techniques to collect the data. Forty students at second semester of English Department in Putera Batam University are taken as the sample. In analyzing the data, researchers classify or categorize the ability of students into six levels: excellent, very good, good, fair, poor, and very poor. Based on the test results, it can be concluded that the ability of second semester students of English Department in Putera Batam University in identifying the singular and plural nouns in a paragraph is good. The results show that three students (7.5%) are categorized as excellent, ten students or 25% are categorized as very good, eleven students (27.5%) are categorized as good, six students (15%) are categorized as fair, six students (15%) are categorized as poor and four students (10%) are categorized as very poor. Therefore, it can be concluded that the ability of students is good.Keywords: singular, plural, paragraf.